Discrimination related HIV and Willingness to Provide Caring HIV Patients among Nursing Students in Samarinda, Indonesia - Khumaidi, Khumaidi; Aisyah, Siti; Solichin, Solichin; Metungku, Fanny (Jurnal Kesehatan Pasak Bumi Kalimantan, 2023)
Background: Misunderstandings, negative attitudes, and unwillingness to care for people with HIV/AIDS are not only shared by health workers. Until now students with it still have understanding, negative attitudes, and an unwillingness to care for people with HIV/AIDS. Objective: to determine the relationship between apprehensive attitudes and the desire of student nurses to provide health services to people with HIV AIDS. Methods: The design used in this research is cross sectional descriptive. This research was conducted at two universities in Samarinda City. Sampling using consecutive sampling technique. Results: there is a significant relationship between calm attitude and the desire to care for patients with HIV AIDS (p value: 0.001). Conclusion: : There is a relationship between attitudes of discrimination and the desire to care for HIV AIDS patients in Diploma Three Nursing students in Samarinda City . Improving the curriculum related to nursing care in patients with HIV AIDS must be comprehensive physical, psychosocial and social